ADAPTIVE FEATURES OF THE VEGETATIVE ORGANS OF SOME COMMON RIPARIAN PLANTS IN THE LOWER HA THANH RIVER, NHONBINH WARD, QUYNHON CITY, BINHDINH PROVINCE - Dương Tiến Thạch; Hoàng Lương Giang (Tạp chí Khoa học Đại học Đà Lạt, 2020)
The plant species which live in the lower Ha Thanh river, Binhdinh province, have some morphological and anatomicaladaptations to the riparianenvironment. The research was carried out on 4 plant species, including trees and grasses in Magnoliopsida, namely Hibiscus tiliaceus L., Excoecaria agallocha L., Ludwigia octovalvis (Jacq.) Raven and Polygonum hydropiper L. The methods used consist of morphological comparison, microsurgery, double staining, measurement and microscopic photography of roots, stems and leaves. The results show suberized stem walls sloughing off easily, lenticels of secondary bark containing nodules or vertical crevices and the development of spongy tissue (33% to 39% of leaf thickness). These features help the plants increase gas exchange. There are small numbers of xylem vessels in the roots (10.33 ± 0.67 vessels/mm2) and stems (22.83 ± 0.75 vessels/mm2) with widths up to 179.17 ± 21.81µm in the roots and 75 ± 9.13µm in the stems. These features allow these species to adjust to the aqueous environment. The supporting tissues in the roots, stems and leaves are very well developed, including xylem and phloem fibers, sclereids and calcium oxalate crystals that help the plants stand firm in extreme conditions, including strong wind and storms.